Experiment on Hemigrapsus takanoi larvae from Kiel Fjord under different tempaerature and salinity levels - Ola Mohamed Nour; Christian Pansch; Meike Stumpp (PANGAEA, 2025)
Ovigerous females were collected by scraping from inner Kiel Fjord in July 2018 and kept under control constant temperature room (~19°C) until egg hatching. Newly hatched larvae were reared under combination of different salinity (6 levels, 10–25) and temperature (19 and 23 °C) treatments in order to estimate the salinity threshold and the interactive role of temperature for larval development in Kiel Fjord Hemigarspus takanoi. Experiments were conducted until larvae reached the megalopae stage (last larval stage) or died. The results of such study could give us a primary outlook on the dispersal ability of H. takanoi larvae along the Baltic Sea.